Improving Student Engagement and Connection in Online Learning through Proactive Support - Chang,Xiaohui (2021)
Xiaohui Chang associate professor of Business Analytics, doesn't hold office hours. She holds "ask me anything hours" as a part of her methods to engage, connect and show empathy for her online students. Her first essay on the Ecampus teaching journey has great tips for all of our increased interactions in the virtual space.
Keywords: Business Analytics